ANALISIS HUKUM PERLINDUNGAN KONSUMEN TERHADAP PEREDARAN E-LIQUID ILEGAL DI DALAM ROKOK ELEKTRONIK - NIM. A1011171217, MOHD. IMAM NASRULLAH (Fakultas Hukum Universitas Tanjungpura, 2024)
ABSTRACT Consumer protection is the totality of regulations and laws that regulate the rights and obligations of consumers and producers that arise in their efforts to meet their needs and regulate efforts to ensure the realization of legal protection for consumer interests. In accordance with the provisions in Law Number 8 of 1999 concerning Consumer Protection, producers must be responsible for losses received by consumers. The title of this research is Legal Analysis of Consumer Protection Against the Distribution of Illegal E-Liquid in Electronic Cigarettes. The type of research used is an empirical research method using non-library studies, namely field research whose object is the symptoms, events and phenomena that occur. in society, Problem formulation